Kesehatan Bank dan Kebijakan Dividen: Pengaruh BOPO terhadap Dividend Payout Tatio pada Bank di BEI 2021–2024 - Saphira Angelia; Tri Joko Prasetio (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
This study examines the relationship between bank soundness measured using the CAMEL approach and the Dividend Payout Ratio of banking companies listed on the Indonesia Stock Exchange during the 2021–2024 period, with particular attention to managerial efficiency represented by BOPO. A quantitative approach with an associative research design is applied. Secondary data are collected from annual financial reports and dividend distribution reports. The sample is selected through purposive sampling, resulting in 20 banks with a total of 80 observations. Data analysis is performed using multiple linear regression with the assistance of SPSS, preceded by descriptive statistics and classical assumption tests. The simultaneous test indicates that CAR, NPL, BOPO, ROA, and LDR jointly influence the Dividend Payout Ratio. The partial test shows that CAR has a significant negative effect on the Dividend Payout Ratio, whereas LDR has a significant positive effect. In contrast, NPL, BOPO, and ROA do not show significant effects at the 5 percent significance level. The coefficient of determination suggests that the CAMEL variables explain only a limited portion of the variation in the Dividend Payout Ratio, indicating that other factors beyond the research model also contribute to banking dividend policy. These findings suggest that dividend policy in the banking sector during the observation period tends to respond more strongly to capital strengthening priorities and intermediation or liquidity dynamics than to credit risk, operational efficiency, or asset profitability.